Assessment of groundwater quality in the different zones of Punjab, north-western India - BHARTI, SURABHI; KAUR, NARINDERJIT; SAINI, SAT PAL (Journal of Soil and Water Conservation, 2022)
The present study was conducted to assess the quality of groundwater in three zones of Punjab on the basis of its depth. For this, a total of 150 water samples, comprising 50 samples from representative village from each district viz. Shri Muktsar Sahib, Ludhiana and Moga were collected during pre- and post-monsoon periods from the main water sources i.e., government rural water supply taps and privately owned submersible pumps. The samples were analyzed for physical and chemical properties for assessing the water quality. Water samples of Killianwali village collected during both monsoon periods, had significantly higher EC, TDS, TS, nitrate, hardness and DO, while the water samples of Rode village had the lowest concentrations. A highly significant and positive correlation of EC and TDS with nitrate was observed during both monsoon periods. Moreover, BOD and turbidity of samples showed highly significant and positive correlation with temperature, whereas, DO showed negative correlation with temperature during both monsoon periods. The principal component analysis showed that water physicalchemical parameters like TDS, nitrate, temperature and hardness of water, were most affected the ground water quality.